8x-(6x-4)=27

Simple and best practice solution for 8x-(6x-4)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(6x-4)=27 equation:


Simplifying
8x + -1(6x + -4) = 27

Reorder the terms:
8x + -1(-4 + 6x) = 27
8x + (-4 * -1 + 6x * -1) = 27
8x + (4 + -6x) = 27

Reorder the terms:
4 + 8x + -6x = 27

Combine like terms: 8x + -6x = 2x
4 + 2x = 27

Solving
4 + 2x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 2x = 27 + -4

Combine like terms: 4 + -4 = 0
0 + 2x = 27 + -4
2x = 27 + -4

Combine like terms: 27 + -4 = 23
2x = 23

Divide each side by '2'.
x = 11.5

Simplifying
x = 11.5

See similar equations:

| m/2+4=m+10 | | n-6=1 | | x+1=.125(x-6) | | 2(4r+5)-12= | | 2x^3-x^2-18x+36k=0 | | 3/4+1/6x=7/24 | | 5j+a=t-2 | | 10x^2+6x=-1 | | 16x-19(x-16)= | | x/-11=-13 | | 2y+3x=44 | | 6+ln(x-5)=8 | | 3/x+1=9/4x+5 | | 53.8-4.8=(0.21) | | 760=40h(200) | | 4z-(2z-5)=3-4(2z+3) | | 21x^2+28x= | | 7/5x-2 | | 9y^2+24y+20=0 | | 3(x-3)-4x=7x+15 | | 154=2x-4(5x-7) | | -13r+5(1-15r)= | | 2y=3x+44 | | 36a^2-12a+1=0 | | 1/2m*2-9n*2-m*2-12+n | | X^2(x-8)+17(x-8)= | | 12x-5=28x+7 | | 5(x-7)+14=2(x-6) | | 2x=3x+44 | | 7x^6-2x^5+x^2+5x+2= | | 4y-12=y+12 | | -1+4+7=2x-9 |

Equations solver categories